Antibacterial agents : chemistry, mode of action, mechanisms of resistance, and clinical applications - Anderson, Rosaleen J.; Wiley InterScience (Online service) (Oxford : Wiley-Blackwell, 2012)
'Antibacterial agents act against bacterial infection either by killing the bacterium or by arresting its growth. They do this by targeting bacterial DNA and its associated processes, attacking bacterial metabolic processes including protein synthesis, or interfering with bacterial cell wall synthesis and function. Antibacterial Agents is an essential guide to this important class of chemotherapeutic drugs. Compounds are organised according to their target, which helps the reader understand the mechanism of action of these drugs and how resistance can arise. The book uses an integrated'lab-to-clinic' approach which covers drug discovery, source or synthesis, mode of action, mechanisms of resistance, clinical aspects (including links to current guidelines, significant drug interactions, cautions and contraindications), prodrugs and future improvements.'--
Introduction to microorganisms and antibacterial chemotherapy -- Agents targeting DNA -- Agents targeting metabolic processes -- Agents targeting protein synthesis -- Agents targeting cell-wall synthesis.
Includes bibliographical references and index.
Print version record.
Keywords: Antibacterial agents; Antibacterial agents; Electronic books